Selection lead logistics provider in consumer goods using AHP – TOPSIS approach - Kuwat Suroto; Hasbullah Hasbullah (Universitas Mercu Buana, 2023)
Vendor selection is a strategic activity in order to support the achievement of the company`s success and competitiveness. Significantly, the company has some specific standards in the selection. Therefore, evaluation is needed to see which vendors match the company's criteria. The purpose of this study was to evaluate and select the proposed vendor in a decision support system using the AHP and TOPSIS approaches. The AHP method is used to determine the importance of the criteria, while the TOPSIS method is used to rank alternatives. The results show that Provider 1 has the highest score compared to other alternatives with a value of 0.852. Sensitivity analysis shows that the proposed AHP and TOPSIS methods are robust, suitable for this problem, and have a low rate of change.